New-onset atrial fibrillation following arteriovenous fistula increases adverse clinical events in dialysis patients with end-stage renal disease - Song, Wenhui; Wu, Lizhou; Sun, Chong; Kong, Xianglei; Wang, Haiyan (Frontiers in Cardiovascular Medicine, 2024)
Background End-stage renal disease (ESRD) patients have a high potential cardiovascular burden, and cardiovascular disease (CVD) is the leading cause of death in maintenance haemodialysis (MHD) patients. Arteriovenous fistula (AVF) is the preferred vascular access for MHD patients, but AVF significantly affects the haemodynamics of the cardiovascular system, leading to or exacerbating CVD, including atrial fibrillation (AF). This study aimed to evaluate the impact of AVF on cardiac function, especially of the left atrium (LA), in patients with ESRD and to further explore the relationship between AVF establishment and the occurrence of AF. Methods We selected 1,107 ESRD patients on haemodialysis using AVF and 550 patients with tunneled-cuffed catheters (TCC) admitted between January 2016 and December 2022 for follow-up to compare the rate of AF between the two groups. A total of 153 patients in the AVF group with complete information (clinical data, echocardiographic and biochemical indices, and other data) were enrolled and retrospectively analysed for risk factors for the development of AF and were followed up for adverse clinical outcomes (including all-cause death, cardiac death, readmission due to heart failure, and stroke). Results The incidence of new-onset AF was higher in the AVF group than the TCC group after dialysis access was established (16.30% vs. 5.08%, P < 0.001). Echocardiography showed that the LA anteroposterior diameter increased (P < 0.001) and the incidence of AF increased from 11.76% to 26.14% (P = 0.001) after AVF establishment. Multivariate logistic regression analysis showed that age and LA enlargement were independent risk factors for new-onset AF after AVF establishment (P < 0.05). Adverse clinical outcomes were more common in patients with AF than in patients without AF (P < 0.001). Multivariate Cox risk regression analysis suggested that new-onset AF (HR = 4.08, 95% CI: 2.00–8.34, P < 0.001) and left ventricular systolic dysfunction (HR = 2.42, 95% CI: 1.20–4.88, P = 0.01) after AVF establishment were independent risk factors for adverse clinical outcomes. Conclusion LA enlargement after AVF establishment is associated with a significant increase in the incidence of AF, in addition, AF which is as an important influential factor in patients with MHD combined other systemic diseases might increase adverse clinical events. Clinical Trial Registration (NCT 06199609)